Promoted methane hydrate formation in -SO3--rich hydrogel clathrate. (1st September 2022) - Wang, Fei; Song, Fu-Peng; Li, Chang; Sun, Meng-Ting
Graphical abstract: Highlights: PSS-co-AAm hydrogel efficiently promoted methane hydrate formation kinetics. -SO3 - groups on hydrogel frameworks facilitated methane hydrate growth. The enlarged gas–liquid interface of micronized hydrogel increased mass transfer. Foaming problem during dissociation process was completely avoided. Swelling ratio in the range of 60 ∼ 120 g g −1 was preferable for hydrogel promotion. Abstract: Natural gas hydrate (NGH) technology holds great promise in natural gas storage and transportation. Utilization of promotor can effectively improve NGH formation kinetics. In this work, we constructed -SO3 - -rich hydrogel clathrate (poly(styrenesulfonate-co-acrylamide), (PSS-co-AAm)) as promoter for methane hydrate formation, with aims of achieving rapid formation rate as well as high storage efficiency. Within swollen PSS-co-AAm hydrogel particles at swelling ratio of 120 g g −1, induction time was 141.0 ± 121.6 min, hydrate growth rate was 0.1773 ± 0.0152 mmol mL −1 min −1, and storage capacity was 110.84 ± 1.01 v/v, indicating that PSS-co-AAm strongly promoted hydrate formation kinetics. This was principally because PSS-co-AAm could accelerate hydrate formation via abundant -SO3 - groups, and meanwhile increase mass transfer via enlarged gas–liquid interface. More importantly, PSS-co-AAm could slightly improve hydrate compactness and completely avoid foaming problem, and meanwhile scarcely cause severe pollution during utilization. The promoting efficiency of PSS-co-AAm were vulnerable to swelling ratio, and the swelling ratio in the range of 60 ∼ 120 g g −1 was preferable. This hydrogel-based promoter was effective and eco-friendly for methane hydrate formation, which might be benefit for large-scale industrialization of NGH technology.